Paraspinal and Extensive Epidural Abscess: The Great Masqueraders of Abdominal Pain. (6th December 2015) - Chu, Andrew; Aung, Thu Thu; Shankar, Uday
Abstract : Paraspinal and epidural abscesses are rare conditions often diagnosed later in the disease process that can have significant morbidity and mortality. Predisposing risk factors include diabetes, human immunodeficiency virus, intravenous drug abuse, and previous history of spinal surgery or injection. They can threaten the spinal cord by compressive effect, leading to sensory motor deficits and ultimately paralysis and death. Diagnosis may be a challenge due to the delayed presentation of nonspecific back pain or radicular pain such as chest pain or abdominal pain. We present a rare case on a patient with periumbilical pain, constipation, and urinary retention who was ultimately diagnosed with a paraspinal abscess extending into the epidural space from T1 to S2. He underwent decompressive laminectomy with incision and drainage of the abscesses. The patient made an excellent recovery postoperatively, and repeat magnetic resonance imaging at six weeks showed resolution of the abscess.